Dual transcriptomics reveals co‐evolutionary mechanisms of intestinal parasite infections in blue mussels Mytilus edulis. Issue 6 (23rd March 2018) - Feis, Marieke E.; John, Uwe; Lokmer, Ana; Luttikhuizen, Pieternella C.; Wegner, K. Mathias
Abstract: On theoretical grounds, antagonistic co‐evolution between hosts and their parasites should be a widespread phenomenon but only received little empirical support so far. Consequently, the underlying molecular mechanisms and evolutionary steps remain elusive, especially in nonmodel systems. Here, we utilized the natural history of invasive parasites to document the molecular underpinnings of co‐evolutionary trajectories. We applied a dual‐species transcriptomics approach to experimental cross‐infections of blue mussel Mytilus edulis hosts and their invasive parasitic copepods Mytilicola intestinalis from two invasion fronts in the Wadden Sea. We identified differentially regulated genes from an experimental infection contrast for hosts (infected vs. control) and a sympatry contrast (sympatric vs. allopatric combinations) for both hosts and parasites. The damage incurred by Mytilicola infection and the following immune response of the host were mainly reflected in cell division processes, wound healing, apoptosis and the production of reactive oxygen species (ROS). Furthermore, the functional coupling of host and parasite sympatry contrasts revealed the concerted regulation of chitin digestion by a Chitotriosidase 1 homolog in hosts with several cuticle proteins in the parasite. Together with the coupled regulation of ROS producers and antagonists, these genes represent candidates that mediate the different evolutionary trajectories within the parasite's invasion. The host–parasite combination‐specific coupling of these effector mechanisms suggests that underlying recognition mechanisms create specificity and local adaptation. In this way, our study demonstrates the use of invasive species' natural history to elucidate molecular mechanisms of host–parasite co‐evolution in the wild.